T.S. Eliot and Adolph Lowe in Dialogue: the Oxford Ecumenical Conference and After - new letters and more about the moot - Schuchard, Margret (Arbeiten aus Anglistik und Amerikanistik, 2006)
Previously unknown letters by T.S. Eliot, written to Adolph Lowe between 1940 and 1960, have now come to light and add another facet to Eliot's longterm contacts with Jewish friends. The eminent poet and the émigré economist shared a profound concern for the future of Europe; they were sure of each other's professional competence, personal integrity and intellectual perspicacity, whether at the Oxford Conference, in the Moot or in any of their public activities. In the course of twenty-five years their initial companionship grew into friendship that lasted, even after Lowe had left for the New School in New York.
Gesehen am 13.01.2021